Reforms in Panchayati Raj: A comparative analysis of Andhra Pradesh, Karnataka and West Bengal - Radhavulu, C.V.; Narayana, E.A (1991)
C.V. Raghavulu and E.A. Narayana present a comparative analysis of reforms that have taken place in panchayati raj institutions in three states of India, i.e., Andhra Pradesh, Karnataka and West Bengal. The authors first describe separately the changes that have been introduced in panchayati raj institutions (PRIs) in the three states before giving detailed comparative analysis of the PR systems in vogue in these states and in the process raise some issues for posible consideration of those involved in reform exercise at the national level. In their comparative analysis, the authors highlight similarities and dissimilarities in the three PRI models relating to structure, composition, devolution of powers, f
Keywords: Panchayati Raj - India; Village Panchayat - India